2002
DOI: 10.1038/sj.eye.6700119
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between nuclear colour and opalescence on the LOCSIII scale and physical characteristics of cataract nuclei

Abstract: Purpose To evaluate the compression characteristics of the human lens nucleocortex in relation to its LOCSIII clinical grading. Methods Sixteen subjects undergoing planned extracapsular cataract surgery had pre-operative slit-lamp examination and assessment of cataract LOCSIII grade followed by postoperative in vitro evaluation of the nucleus with measurement of 'linear compressibility' by a purpose-designed caliper incorporating a strain gauge, enabling the derivation of a graph of nuclear compression (D (mm)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 30 publications
(34 reference statements)
2
19
0
Order By: Relevance
“…Smith et al 16 have shown that nuclear opacity correlates well with in vitro measured hardness of the human lens. Another study 17 has found that a higher phacoemulsification energy is required as the severity of nuclear cataract increases.…”
Section: Discussionmentioning
confidence: 95%
“…Smith et al 16 have shown that nuclear opacity correlates well with in vitro measured hardness of the human lens. Another study 17 has found that a higher phacoemulsification energy is required as the severity of nuclear cataract increases.…”
Section: Discussionmentioning
confidence: 95%
“…The cataracts were graded according to the Lens Opacities Classification System III (LOCS III) grading scale. 12,13 Inclusion criteria included a nucleus hardness of LOCS III grade 2 or 3. Exclusion criteria were corneal pathology, inflammatory eye disease, glaucoma, endothelial cell density less than 1500 cells/mm 2 , previous ocular surgery or trauma, and diabetes mellitus.…”
Section: Methodsmentioning
confidence: 99%
“…Here we should note that in ophthalmic literature, there is often a confusion between the terms 'hardness' and 'stiffness,' which is at least partly due to different definitions of hardness [34]. While stiffness defines the relationship between stress and strain, lens hardness is often measured by penetration/ guillotine experiments, so that it depends on the force at which the material breaks.…”
Section: Lens Changes and Stiffness Profilesmentioning
confidence: 99%